ANALISIS GERAK DASAR ANAK USIA 6-7 TAHUN - Kurniawan, Rama (Jurnal Pendidikan Usia Dini, 2018)
This study aims to know the students’ fundamental movement ability and to analyze those movements based on gender. It was conducted in SDN 1 Lemahabang Kulon, Cirebon Regency. The subject involved in this study was 24 students of the lower-primary levels in the school whose ages between 6-7 years old. Data collection method applied was the observation of the students’ fundamental movements. The assessment form on fundamental movement (Gallahue :1996) was used as the instrument of the study. The data was analyzed using a descriptive quantitative technique with a percentage. The finding shows that it was only 65.6 % students who properly mastered the fundamental movement of stability. Meanwhile, the fundamental movements of locomotor and manipulative were mastered only by 43 % and 41.7 %. Based on the gender analysis, the male students were better on fundamental movements than the female ones. To facilitate the future success of movement on students, it is suggested to have a directional and specific program on movement development. Keywords:, Early childhood, Fundamental movement Penelitian ini bertujuan untuk mengetahui kemampuan gerak dasar siswa serta menganalisa gerakan tersebut berdasarkan gender. Penelitian ini dilakukan di SDN 1 Lemahabang Kulon Kabupaten Cirebon. Subyek yang terlibat dalam penelitian adalah siswa sekolah dasar kelas rendah yang berusia 6-7 tahun yang berjumlah 24 anak. Pengumpulan data dalam penelitian ini menggunakan kegiatan observasi terhadap gerakan dasar siswa. Instrumen yang digunakan adalah format penilaian gerak dasar. Analisis data yang digunakan adalah deskriptif kuantitatif dengan menggunakan persentase. Hasil penelitian menunjukkan bahwa hanya 65.6% siswa yang menguasai dengan baik gerak dasar non-lokomotor. Sedangkan gerak dasar lokomotor dan manipulatif hanya 43% dan 41.7%. Berdasarkan analisis gender, siswa laki-laki memiliki kemampuan gerak dasar yang lebih baik daripada siswa perempuan. Untuk mendukung kesuksesan gerak siswa di masa mendatang, diperlukan program pengembangan gerak yang terarah dan spesifik. Kata Kunci: Anak usia dini, Gerak dasar